PENGARUH MODEL PEMBELAJARAN MAKE A MATCH TERHADAP KONSENTRASI SISWA SEKOLAH DASAR DALAM PEMBELAJARAN BAHASA INDONESIA - Juliani, Intan; Puspita, Yenny; Purnama Sari, Syska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of the "Make A Match" cooperative learning model on the learning concentration of fourth-grade students in the Indonesian language subject. The study was motivated by the students' low learning concentration, which resulted in suboptimal engagement during the learning process. A quantitative approach was employed using a pre-experimental design—specifically, the one-group pretest-posttest design. The research sample consisted of 33 students from class IV-A at SD Negeri 04 Palembang, selected using a purposive sampling technique. Data were collected via a learning concentration questionnaire that met validity and reliability standards. Data analysis included the Shapiro-Wilk normality test and the paired-sample t-test. The results showed that the students' average learning concentration score increased from 56.06 in the pretest to 70.42 in the posttest. The paired-sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. These findings demonstrate that the implementation of the "Make A Match" learning model has a significant effect on improving the learning concentration of fourth-grade students in the Indonesian language subject.